11 Stat. at Large of Pa. 209, ch. 1059, §§ 1-2 (1782) - (:unkn) unknown (My University, 1783)
all gun-powder brought into the port of Philadelphia should be deposited in a certain powder house therein described, under the penalty of ten pounds for every offense: And Whereas another powder house or magazine hath been erected in the said city in the public square on the south side of Vine street, between the Sixth and Seventh streets from Delaware at the public expense
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER